An analysis of the impact of gender based violence against men in Mutare District. case of Burma Valley Ward 27. - Gudyanga, Tendai Julia (Midlands State University, 2020)
This study focused on GBV against men which is something that is rarely talked. The worst part of GBV against men is that, when it does get talked about, discussion is almost always limited to the abuse that men do to women. A lot of people are of the idea that violence is not something that women do, and when the men who have been victims of women try to speak out they frequently encounter negative reactions like mockery and name calling to actual accusations like it is their own fault that they were abused. It is worse when those reactions come from the people of the law who are supposed to be protecting the same people. In addition, there is no excuse for any human rights body to deny GBV against men or to attack any man for discussing and sharing their experiences of it.